The influence of e-commerce live streaming features on consumer trust and purchase intention in Malaysia: a study of Malaysia univeristy students - Lai, Jing Yu (2025)
This study examines the influence of e-commerce live streaming features on consumer trust and purchase intention, focusing on Malaysian university students. Grounded in the Stimulus–Organism–Response (S–O–R) model, the study investigates how three key live-streaming features which are authenticity, entertainment, and interactivity affect consumer trust and subsequently influence purchase intention.